Changes in expression of inflammatory cytokines and ocular indicators in pre-diabetic patients with cataract - Yixun Chen; Yan meng; Mengjia Tan; Jun Ma; Jian Zhu; Min Ji; Huaijin Guan (BMC Ophthalmology)
Abstract Pre-diabetes is the preceding condition of diabetes, and in some cases, fundus changes have been seen in pre-diabetes. The inflammatory response is widely recognized as being involved in the pathophysiologic process of diabetic eye disease. Therefore, we aimed to acquire understanding of the role of early altered blood glucose levels in the development and etiology of diabetic ocular disorders from the perspective of inflammation. In this study, serum, tear, aqueous humor and vitreous fluid samples were collected from patients undergoing cataract surgery. VEGF, IL-6, TNF-a, MCP-1, APOA-1, ICAM-1, VCAM-1, PEDF, TSP-1 were measured by ELISA. The quantity of hyperreflective retinal spots (HRS) was counted by optical coherence tomography OCT images. We found that the levels of inflammatory cytokines are already altered in pre-diabetes. Levels of pro-inflammatory cytokine expression and quantity of HRS can reflect the disease process to some extent.